2014
DOI: 10.1371/journal.pone.0102971
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Emotion Regulation Difficulties on the Tonic and Phasic Cardiac Autonomic Response

Abstract: BackgroundEmotion regulation theory aims to explain the interactions between individuals and the environment. In this context, Emotion Regulation Difficulties (ERD) disrupt the physiological component of emotions through the autonomic nervous system and are involved in several psychopathological states.ObjectiveWe were interested in comparing the influence of a film-elicited emotion procedure on the autonomic nervous system activity of two groups with different levels of emotion regulation difficulties.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 80 publications
(95 reference statements)
3
60
1
2
Order By: Relevance
“…Although not pathological in and of itself, greater affective intensity may lead individuals with GAD to adopt a rigid and defensive stance in efforts to cope with emotions that feel overwhelming or threatening (e.g., Mennin and Fresco 2014). Further, non-diagnosed individuals with high levels of difficulties in regulating emotions show a pattern of HRV response similar to that typically found in GAD: in a recent study, although HRV in both low- and high-difficulties groups decreased in response to negative emotion, the high-difficulties group showed a prolonged decrease that persisted beyond the elicitation into the recovery period (Berna et al 2014). Decreased HRV has also been linked to facets of emotion regulation deficits relevant to GAD—namely lack of emotional clarity and lower inhibitory control when experiencing negative emotions—even after controlling for anxiety and other covariates, supporting the link between physiological flexibility and adaptive response to emotion (Appelhans and Luecken 2006; Williams et al 2015).…”
Section: Discussionmentioning
confidence: 52%
“…Although not pathological in and of itself, greater affective intensity may lead individuals with GAD to adopt a rigid and defensive stance in efforts to cope with emotions that feel overwhelming or threatening (e.g., Mennin and Fresco 2014). Further, non-diagnosed individuals with high levels of difficulties in regulating emotions show a pattern of HRV response similar to that typically found in GAD: in a recent study, although HRV in both low- and high-difficulties groups decreased in response to negative emotion, the high-difficulties group showed a prolonged decrease that persisted beyond the elicitation into the recovery period (Berna et al 2014). Decreased HRV has also been linked to facets of emotion regulation deficits relevant to GAD—namely lack of emotional clarity and lower inhibitory control when experiencing negative emotions—even after controlling for anxiety and other covariates, supporting the link between physiological flexibility and adaptive response to emotion (Appelhans and Luecken 2006; Williams et al 2015).…”
Section: Discussionmentioning
confidence: 52%
“…Extensive research has indicated that individuals who are better at regulating their emotions have better physical and mental health outcomes (Aldao, Nolen-Hoeksema, & Schweizer, 2010;Florin, Freudenberg, & Hollaender, 1985;Greer & Watson, 1985;Hu et al, 2014;Verzeletti, Zammuner, Galli, & Agnoli, 2016). For example, emotion dysregulation has been associated with increased risk for cardiovascular disease (Appleton & Kubzansky, 2014;Berna, Ott, & Nandrino, 2014).…”
Section: Emotion Regulation and Health Indicatorsmentioning
confidence: 99%
“…Vagally mediated HRV (vmHRV) is strongly associated with emotion regulation and underpins individual differences in the perception of emotional stimuli (Park et al, 2013). It predicts affective instability in daily life (Koval et al, 2013) and is inversely correlated to greater reports of difficulties in emotion regulation (Berna et al, 2014;Williams et al, 2015). While emotional dysregulation is a core feature of BPD itself, it may also be an important candidate to explain high rates of comorbidity between BPD and other mental disorders (e.g.…”
Section: Introductionmentioning
confidence: 99%